Systematic Literature Review : Jenis Kesalahan Pembuktian Matematis Siswa - Patimah Hasibuan; Rusi Ulfah Hasanah; Siti Jubaidah; Siti Khadijah Nasution (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Mathematics is the mother of science which plays an important role in the development of all aspects of the field of science due to the nature of dependence on all fields of various scientific disciplines. The research method used in this research is the literature study method. This study states that learning to solve problems plays an important role in mathematics, which is almost the same as other conventional roles. Core competencies and competencies were discovered that focus on the need for problem solving skills. The conclusion from various studies conducted using literature studies can be concluded that the weakness is that students have difficulty carrying out mathematical proofs and are less careful when carrying out proofs